How narratives influence colorectal cancer screening decision making and uptake: A realist review - Anke Judith Woudstra; Jeanine Suurmond (Wiley, 2019)
Abstract Background Although narratives have been found to affect decisions about preventive behaviours, including participation in cancer screening, the underlying mechanisms of narratives remain unclear. Objective The purpose of this study was to summarize and synthesize existing literature on narrative interventions in the context of colorectal cancer screening. Our main research question was as follows: How, when and for whom do narratives work context of decision making about colorectal cancer screening participation? Methods We undertook a realist review to collect evidence on narratives in the context of colorectal cancer screening. A search of the literature was performed in Embase, MEDLINE/PubMed, Cinahl and PsycINFO. We included empirical evaluations (qualitative or quantitative) of narrative interventions. In total, 15 studies met the inclusion criteria. A content‐based taxonomy of patient narrative types in decision aids formed the basis for our initial programme theory. Main result We identified four mechanisms: (a) process narratives that address perceived barriers towards screening lead to improved affective forecasting, (b) experience narratives that demonstrate the screening procedure lead to increased self‐efficacy, (c) experience narratives that depict experiences from similar others lead to more engagement and (d) outcome narratives that focus on outcomes of colorectal cancer (CRC) screening decision decrease or increase fear of colorectal cancer. The evidence was limited on which narrative type may facilitate or bias informed decision making in colorectal cancer screening. Discussion and conclusion The findings indicate the importance of more detailed descriptions of narrative interventions in order to understand how mechanisms may facilitate or bias informed decision making in colorectal cancer screening.